Investigation of the Africa splitting into two as new ocean forms - Atınç Pırtı (Geodesy and Cartography)
Scientists believe that Ethiopian tectonic plate changes indicate that Africa is breaking apart, opening the path for the emergence of the planet’s sixth ocean. Ever since the East African Rift, a 35-mile-long fissure in Ethiopia’s desert, appeared in 2005, there has been a continuous movement between the tectonic plates. The second-largest continent in the world will virtually split in two due to the separation of the Somalian tectonic plate from the larger Nubian tectonic plate. This event has not been seen in hundreds of millions of years, when South America and Africa were separated into separate continents. The Somali and the Nubian tectonic plates are slowly disintegrating from each other, while the Arabian plate continues to pull away. The continental rift will happen along the east African Rift Valley, a geologically active region whose formation millions of years ago is similar to that of the tectonic movements that happen at the bottom of oceans. This means landlocked countries such as Rwanda, Uganda, Burundi, the Democratic Republic of Congo, Malawi, and Zambia would inadvertently find themselves with a coastline, and thus, build harbours that connect them to the rest of the world directly. Kenya, Tanzania, and Ethiopia would have two territories each. Though that will take between five to 10 million years, the continent will eventually split into two sub-continents, creating a new ocean basin between them.